Case Report: A Rare Syncope Case Caused by Abernethy II and a Review of the Literature - Lin, Xue-qin; Rao, Jing-yi; Xiang, Yi-fei; Zhang, Li-wei; Cai, Xiao-ling; Guo, Yan-song; Lin, Kai-yang (Frontiers in Cardiovascular Medicine, 2022)
Background: Abernethy malformation is an extremely rare anomaly of the splanchnic venous system, and only 2 cases that manifested as syncope had been reported previously. Case presentation: A 24-year-old male had a 15-year history of jaundice and was in long-term use of hepatoprotective drugs. He was admitted for complaint of syncope. He underwent a series of examinations and cardiac ultrasound showed that his pulmonary artery pressure was elevated. Further imaging revealed the absence of intrahepatic portal veins. His blood ammonia was significantly increased. All signs and symptoms pointed to an Abernethy diagnosis. He was finally diagnosed as having Abernethy type II. He was discharged after 17 days of in-hospital treatment with sildenafil (50 mg/day) and ornithine aspartate (20 g/day). Conclusion: We now report this rare case of syncope that is caused by Abernethy malformation. As a typically pediatric disease, it was not identified in this patient until adulthood due to long-term treatment for jaundice and liver cirrhosis. Furthermore, we present a review of portosystemic shunts previously reported in the literature.